2018
DOI: 10.3390/su10082957
|View full text |Cite
|
Sign up to set email alerts
|

A Drivers-Pressure-State-Impact-Responses Framework to Support the Sustainability of Fish and Fisheries in Lake Tana, Ethiopia

Abstract: Lake Tana, Ethiopia's largest lake, has a remarkable and conservation-worthy assemblage of fish species, requiring fisheries management for sustainable exploitation. However, due to anthropogenic impacts, many of these fish species are threatened. Hence, an improved management of these resources is recommended. To allow a more sustainable exploitation of natural resources, a better understanding of the cause-effect relationships between anthropogenic impacts and environmental components is fundamental. The Dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 63 publications
4
64
0
2
Order By: Relevance
“…A decline in juvenile labeobarb abundance in the pool habitats of Gumara River occurred because of excess irrigation water abstraction, especially in the dry season months of March to May [44]. In addition, several studies found that in recent years, fish stocks declined rapidly, especially commercially important fish species like Labeobarbus' which are migratory fishes requiring wetland habitats for breeding [23,32,45]. From these results, we infer that the river is becoming disconnected earlier from the floodplain wetlands because of a decrease in "ecologically relevant" large floods.…”
Section: Low and High Flowsmentioning
confidence: 99%
“…A decline in juvenile labeobarb abundance in the pool habitats of Gumara River occurred because of excess irrigation water abstraction, especially in the dry season months of March to May [44]. In addition, several studies found that in recent years, fish stocks declined rapidly, especially commercially important fish species like Labeobarbus' which are migratory fishes requiring wetland habitats for breeding [23,32,45]. From these results, we infer that the river is becoming disconnected earlier from the floodplain wetlands because of a decrease in "ecologically relevant" large floods.…”
Section: Low and High Flowsmentioning
confidence: 99%
“…Given that the situation of the Mar Menor goes beyond mere environmental problems, it is necessary to establish a framework that approaches the situation from a multidisciplinary focus in which it is possible to involve all stakeholders. Stakeholders have been selected following a DPSIR (Driving forces, Pressure, State, Impact, and Response) model [55] (Figure 3).…”
Section: Integrated Diagnosismentioning
confidence: 99%
“…Given that the situation of the Mar Menor goes beyond mere environmental problems, it is necessary to establish a framework that approaches the situation from a multidisciplinary focus in which it is possible to involve all stakeholders. Stakeholders have been selected following a DPSIR (Driving forces, Pressure, State, Impact, and Response) model [55] (Figure 3). During the first stage (Driving Forces), a preliminary analysis has been carried out through which the most significant elements of the problem and possible information prescribers have been determined.…”
Section: Integrated Diagnosismentioning
confidence: 99%
“…have different FL 50% [30], using a stretched mesh size of ≥ 10 cm is most advisable. In addition to mesh size restriction, we suggest the following management options for successful conservation of the lake fish and fisheries: (1) limitation of the number of fishers and fishing gears, (2) application of a hybrid bottom-up and top-down approach to identify problems, make decision and enforce the regulations [8], (3) limitation of the amount of landing sites, (4) provision of license to all fishers, (5) hire fishery inspectors, (6) establish standard data acquisition protocols and gather fisheries information regularly, (7) revision (e.g., incorporate development issues such as sand mining and damming) and proper implementation of regulations, and (8) continuous monitoring and assessment. Therefore, we suggest the local fisheries authorities incorporate these management options in the Lake Tana fish and fisheries management plan.…”
Section: Management Strategiesmentioning
confidence: 99%